Rediscovering the art of Developmental Therapy: an interview with Mary M. Wood - Teagarden, James M.; Kaff, Marilyn S.; Zabel, Robert H. (My University, 2013)
Dr. Mary Margaret Wood is best known for developing psycho-educational programs that integrate mental health and special education interventions for children with emotional and behavioral disorders (EBD). Developmental Therapy (DT) includes comprehensive assessment of student behavior, communication, social, and cognitive development, individualized interventions to facilitate healthy personality growth across the developmental frameworks, and on-going monitoring of student development. Developmental Therapy Teaching (DTT) offers educational approaches for educators and other interveners and places developmentally-matched objectives and instructional strategies at the center of the intervention process. Over the past 40 years, DT and DTT and elements of these models have been adopted both nationally and internationally. In this interview, Dr. Wood reflects on her career, influences on the development and contributions of Developmental Therapy, the current status of the field, and the future of educating children with EBD. The interview was conducted on August 16, 2011 in Athens, Georgia, where Dr. Wood is Professor Emeritus of Special Education at the University of Georgia.
Keywords: Wood, Mary M.; Developmental therapy; Special education interventions; Emotional and behavioral disorders